Combining ability study on yield and its contributing traits in maize (Zea mays L.) - Sharma, Prashant; Chandel, Uttam (Journal of Cereal Research, 2022)
Experimental material consisted of 25 lines, 2 testers and their 50 crosses along with standard checks viz., Palam Sankar Makka-2 and PSCL 4640 were evaluated using Randomized Block Design with two replication during Kharif 2020. Genotype mean square was significant for days to 50% tasseling, days to 50% silking, days to 75% brown husk, ear height (cm), plant height (cm), ear length (cm), ear circumference (cm), kernel rows/cob, kernels/row, 1000-kernel weight (g), shelling (%) and grain yield (q/ha) which indicated the presence of sufficient genetic variability in the material studied. Also the ratio of GCA variance to SCA variance was less than unity for all traits indicated preponderance of non-additive gene action. Among lines, KI-3 exhibited higher grain yield followed by KI-7 and CML 140. These lines also exhibited highest significant GCA effect for grain yield and were identified as promising parents. KI-7 × LM 13, CML 140 × LM 13, CML 139 × LM 13, CML 162 × LM 13 and KI-3 × LM 14 exhibited maximum SCA effect for most of traits. These promising cross combinations need to be evaluated in multi-location trials over the years to assess their suitability in different agro-climatic zones of the State.